PEMBENTUKAN IDENTITAS BARU TOKOH IMIGRAN DALAM EMPAT CERPEN KARYA DUA PENGARANG BERLATAR BELAKANG IMIGRAN WLADIMIR KAMINER DAN DILEK GÃ¼NGÓ§R - Hawa, Andina Meutia; Rahayu, Lina Meilinawati; Purnomowulan, N. Rinaju (Balai Bahasa Jawa Timur, 2017)
This research aims to reveal the depiction of formation of the new identity of immigrant characters in four short stories written by two immigrant authors in contemporary German literature, Wladimir Kaminer and Dilek Güng?r. This study discusses how the immigrant characters build their new identities and their self-subjectivities in four short stories, namely ?Schlechte Vorbilder?, ?Deutsch-russisch Kulturjahr?,